Testing specimens for Chlamydia trachomatis - Skidmore, S (BMJ Group, 2006)
The introduction of NAATs has revolutionised chlamydial diagnostics and these tests are now the standard of care. However, as with all new technologies, they have also presented new challenges. This review attempts to answer some of the questions that have been raised, particularly by groups about to embark on implementing a screening programme. Laboratory tests are continually changing but it is hoped that the paper provides a useful update of the current situation.